Macroalgae biomass, epiphytic biomass on seagrass and phytoplankton biomass in Changuu Island (Zanzibar Archipelago, Tanzania) at end of nutrient enrichment and macrofauna exclusion experiment - Agustín Moreira-Saporiti; Mirta Teichberg; Aoife O extquotesingleSullivan (PANGAEA, 2026)
Macroalgae biomass, epiphytic biomass on seagrass and phytoplankton biomass in the water column was taken at the end of a nutrient enrichment and macrofauna exclusion experiment. A total of 24 plots were set up parallel to the shore, with presence of the three seagrass species (Syringodium isoetifolium, Thalassodendron ciliatum and Thalassia hemprichii) in each plot. The experiment was the factorial combination of two treatments: macrofauna exclusion using cages (three levels: open, closed and uncaged) and nutrient enrichment using garden NPK fertilizer (two levels: ambient and enriched). Each treatment combination was replicated four times. Exclusion treatment simulates the consequences for the food web of losing a top predators and macrograzers. Nutrient enrichment was simulated by issuing nitrogen-phosphorus-potassium (NPK) [15:9:20] fertilizer pellets. NPK fertilizer fast release pellets were packed into cotton tubes and then into a perforated plastic tubes to simulate slow release of nutrients. The tubes were buried half-way into the sediment to ensure enrichment of both the water column and the sediment. Data was collected at the end of the experiment (Day 63, 19.09.2017). Data collection and experiment took place in Changuu Island (Zanzibar Archipelago, Tanzania; 0611 extquotesingleS, 3916 extquotesingleE). Changuu Island is located 3 km from Stone Town, Zanzibar extquotesingles busiest town. Changuu remains relatively unaffected by nutrient runoff pollution. The study area is characterised by a fringing reef around a multi-specific seagrass ecosystem. The substrate is primarily carbonate sediment. Average water depth is approximately 30 cm at Spring Low and 5 m at Spring high tide with an average depth of 2 m. Macroalgae biomass, epiphyte biomass on seagrass and phytoplankton biomass was collected in each experimental plot to study the effect of nutrient enrichment and macrofauna exclusion on the primary producers in the ecosystem. To determine the abundance of macroalgae in the different treatments, the macroalgae biomass was collected at the end of the experiment by removing all visible macroalgae present in the experimental plots. Macroalgae was rinsed with freshwater and dried in the oven at 60°C for 48 hours until constant dry weight. The final dry weight was then divided by the treatment plot surface to obtain g DW m-2. To determine phytoplankton biomass under the different treatments, we quantified Chlorophyll-a concentrations in the water column. Water was collected in a 2-litre bottle from each of the 24 plots at the end of the experiment. The water bottles were kept in the dark in a cooler box upon arrival to the lab and water was then filtered under constant pressure onto pre-combusted (5 h, 450?C) and pre-weighed Whatman GF/F filters (0.45-μm pore size). Chlorophyll-a was then extracted from the filters in 8 ml of 96% ethanol in glass vials heated for 5 min at 80?C, covered with aluminum foil, and placed in a rotor at room temperature for 24 h. Extracts were subsequently centrifuged at 5,000 rpm for 20 min. Chlorophyll-a absorbance of the supernatant was determined in a Shimadzu UV-1700 photometer, and calculated as μg Chl l-1. To determine epiphyte biomass in the treatments, one seagrass shoot per species was collected at each treatment plot at the end of the experiment. Each shoot was collected in a white mesh bag (<1 mm mesh size). In the laboratory, samples were carefully rinsed in freshwater and all epiphytes were scraped off. The scraped epiphytic biomass was dried at 60° C for 48 hours until constant dry weight, and then weighed (mg DW). The epiphytic biomass was then multiplied by the shoot density of each species. This was then summed to obtain the total epiphytic biomass per unit of area (g DW m-2).